Upaya Peningkatan Pengetahuan Bencana melalui Prototipe Aplikasi LANDIE (Landslide Disaster Education) - Muhammad Naufal Fajri Assidiqi; Juhadi Juhadi; Eva Banowati (Universitas Negeri Gorontalo, 2023)
The high incidence of landslides during the rainy season still occurs frequently. Efforts have been made to increase knowledge about landslide disasters among the public. The use of technology through applications in providing knowledge about landslide disasters generally uses text and images. To address this gap, we developed a new application prototype with disaster knowledge and evacuation route navigation features called LANDIE (Landslide Disaster Education). The method used is quantitative descriptive in the form of mean and standard deviation analysis; descriptive percentage; kolmogorov-smirnov and paired sample t-test. The research results reveal that the LANDIE application prototype is effective in increasing knowledge of landslide disasters. This is supported by the findings that initial knowledge about landslide disasters is at medium criteria, with the application design being suitable for use with revisions, the application is suitable for use as a medium in disaster training, and the LANDIE application prototype is declared effective in increasing knowledge about landslide disasters.